The Integration Processes Impact within the EAEU on the Russian Economy - Mayorova M.A., Shkiotov S.V., Markin M.I., Ugryumova M.A, (Opción, 2019)
The purpose of this paper is to assess the impact of integration processes within the EEU on the Russian economy using the methods of economic and mathematical modeling. As a result of the research, it was established that the hypotheses stated in the research in the long-term time interval were not confirmed. In conclusion, there is a strong feedback between the dynamics of foreign trade turnover in the EEU countries and the level of competitiveness of the Russian economy, as well as the quality of life of the population.